The postoperative fall in platelet count in cancer: Mirroring the catastrophe? - Mishra, Shubhangi Durgakumar (J Oral Maxillofac Pathol, 2018)
INTRODUCTION: Progression of cancer requires the growth and invasion of the tumor at its parent site as well as metastasis. Recent studies have shown that tumor cells can aggregate platelets in vitro (a process termed tumor-cell-induced platelet aggregation [TCIPA]), and this aggregation correlates with the metastatic potential of cancer cells in vivo. Platelet depletion or even an inhibition of TCIPA reliably diminishes metastasis. Furthermore, tumor cells bind platelet adhesion receptors of circulating platelets to metastasize more effectively. Studies say that malignant tumors to interact with platelets in the above fashion secrete platelet activating factors which raise the platelet count in malignancy. The study undertaken aims at comparing the preoperative and postoperative platelet levels in patients with benign and malignant neoplasms. MATERIALS AND METHODS: With an appropriate sample size of patients with benign or malignant neoplasms as per the inclusion and exclusion criteria, a platelet count presurgically and the 7(th) day postsurgically was advised. RESULTS: In case of patients with benign neoplasms, the postoperative platelet count showed a significant rise attributed to a normal healing response, while in patients with malignant neoplasms, the platelet count appeared to fall down significantly due to the effect of tumor removal and therefore a diminished production of thrombopoietic cytokines. The results obtained were thus consistent with the theories of tumor cell-platelet interactions proposed in the recent literature so far. CONCLUSION: Postoperatively, the platelet count rises in the patients with the benign tumor as a result of a normal healing response while those in patients with malignant neoplasm apparently appears to fall down due to the effect of tumor removal thus diminishing the production of platelet activating factors.